Financiamento eleitoral e comportamento parlamentar: A relaç\~ao entre doaç\~oes da indústria e proposiç\~ao de leis - Wagner Pralon Mancuso; Manoel Leonardo Santos; Ciro Antônio da Silva Resende; Danilo Praxedes Barboza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This study investigates the relationship between electoral donations made by industrial entrepreneurs and the behavior of federal deputies elected for the 54th legislature (2011-2015), with regard to the presentation of legislative proposals favorable or contrary to the interests of that business sector. The effect of campaign financing is controlled by the effect of a number of other variables potentially relevant to the phenomenon of interest. The results show that industrial electoral contributions favor the presentation of bills that converge with the interests of the donors, but do not prevent the presentation of other bills rejected by that economic sector.
Keywords: D72; 330; campaign financing; legislative behavior; Chamber of Deputies